Mucous Cyst at the Interphalangeal Joint of the First Toe Caused by Contact Pressure With the Second Toe due to Hallux Valgus - Ichiro Tonogai MD, PhD; Yuhei Yamasaki MD; Toshihiko Nishisho MD, PhD; Koichi Sairyo MD, PhD (Foot & Ankle Orthopaedics, 2018)
A 77-year-old woman presented with a mucous cyst on the lateral aspect of the interphalangeal joint of the first toe caused by contact pressure with the second toe from hallux valgus. She complained of discomfort and discharge from the left first toe for approximately 4 months. Physical examination showed the second toe pressing strongly against the first toe due to hallux valgus and discharge from the skin on the lateral aspect of the interphalangeal joint of the first toe. Magnetic resonance imaging showed a cystic lesion at the same level. The patient underwent a modified scarf osteotomy of the first metatarsal for hallux valgus to resolve the contact pressure between the toes— considered the cause of the mucous cyst—and resection of mucous cyst. Forefoot weight bearing was allowed 6 weeks after surgery. As of 1 year after surgery, she has had no recurrence of the cyst. The score on the Japanese Society for Surgery of the Foot hallux metatarsophalangeal-interphalangeal scale improved from 59/100 points to 92/100. This outcome suggests that hallux valgus correction should be considered when a mucous cyst is associated with contact pressure due to a hallux valgus deformity. To the best of our knowledge, there are no previous reports of a mucous cyst caused by contact pressure between the first toe and second toe due to hallux valgus.